Pengaruh Net Profit Margin dan Total Assets Turnover Terhadap Return Saham - Widya Cahyani Wibisono; Dirvi Surya Abbas; Indra Gunawan Siregar (BADAN PENERBIT STIEPARI PRESS, 2024)
The purpose of this study is to determine the effect of Net Profit Margin, Earning Per Share and Total Assets Turnover in manufacturing companies in the food and beverages listed on the Indonesian Stock Exchange for the 2016-2020 peiod. The sampling technique used was purposive sampling technique. Based on the predetermined criteria obtained 16 companies. The type of data used is secondary data obtained from Indonesia Stock Exchange website (www.idx.co.id). The analytical methode used is panel dat a regression analysis. The results showed that the t-statistic of NPM 2.537863 > T table of 1.99125 and the prob value of table of 1.99125 and the prob value of 0.0382 < 0,05, it can be conclude that H2 is accepted. T statistic TATO -0204088 > T table is 1.199125 and the prob value is 0.8388 > 0.05, so it can be concluded that H3 is rejected. Net Profit Margin, Earning Per Share affect Stock Returns, while Total Assets Turnover has no effect on Stock Returns.